Multipolarity in Development Banking: The Asian Infrastructure & Investment Bank (AIIB) and Asian Development Bank (ADB) - Widjanarko, Yeremia Nicolaus (Jurnal Ilmu Ekonomi Terapan, 2024)
This research analyzed multipolarity in development financing, focusing on the Asian Infrastructure Investment Bank (AIIB) and the Asian Development Bank (ADB). These two banks represent a shift in global economic power from the West to the Far East, particularly with the rising role of China. Using the Neorealism theoretical framework, the research examined the political-economic differences, leadership structures, and financing patterns of AIIB and ADB. The data showed that AIIB and ADB significantly differ in membership, objectives, initial capital, geographical coverage, environmental policies, and relationships with major economies such as China, Japan, and the United States. Their financing patterns across various Asian economies, such as India and Bangladesh, reflect a more balanced power distribution and the resilience of the international system. Additionally, the flexible approach of AIIB contrasts with ADB’s stricter conditionality, highlighting differing strategies in development financing. The findings indicate that multipolarity in development financing enhances stability and order in the international system, consistent with Neorealism’s view on the importance of natural power competition. The presence of both institutions encourages innovation and adaptation, contributing to a more robust and diverse global financial architecture.